Pemutusan Hubungan Kerja (PHK) terhadap Karyawan Terdampak Pandemi Covid-19 - Mokh. Thoif (Perspektif Hukum, 2022)
The COVID-19 pandemic has occurred in almost all parts of the world, resulting in enormous changes, especially in various business circles. This study aims to examine the termination of employment due to the COVID-19 pandemic in terms of the Job Creation Act. The writing method uses a normative legal approach that relies on laws, reference materials, and documents relevant to the legal issues being studied. Based on the results of the study, it can be stated that layoffs are allowed in the conditions of the COVID-19 pandemic because the pandemic is classified as a forced emergency. Furthermore, the existence of such layoffs provides legal consequences for business actors who are obliged to pay workers in the form of legal protection for workers in the form of severance pay, award money. period of service and compensation for entitlements.